Stalagmite δ18O record from Básura cave (northern Italy) since the middle Holocene - Hsun-Ming Hu (PANGAEA, 2025)
This dataset comprises oxygen isotope (δ^1?O) records derived from two stalagmites, BA14-1 and BA18-4, collected from Bàsura Cave in the Liguria region of northern Italy. The combined records provide a continuous proxy spanning from approximately 6500 years before present to around 1950 AD. The aim of this data collection is to reconstruct high-resolution hydrological and climatic changes in northern Italy, thereby offering valuable insights into past water cycle dynamics and regional climate variability over millennial to centennial timescales.